Post-stroke cognitive impairments and responsiveness to motor rehabilitation: A review - VanGilder, Jennapher Lingo (Curr Phys Med Rehabil Rep, 2020)
a). PURPOSE OF REVIEW: This review discusses the prevalence of cognitive deficits following stroke and their impact on responsiveness to therapeutic intervention within a motor learning context. b). RECENT FINDINGS: Clinical and experimental studies have established that post-stroke cognitive and motor deficits may impede ambulation, augment fall risk, and influence the efficacy of interventions. Recent research suggests the presence of cognitive deficits may play a larger role in motor recovery than previously understood. c). SUMMARY: Considering that cognitive impairments affect motor relearning, post-stroke motor rehabilitation therapies may benefit from formal neuropsychological testing. For example, early work suggests that in neurotypical adults, cognitive function may be predictive of responsiveness to motor rehabilitation and cognitive training may improve mobility. This sets the stage for investigations probing these topics in people post-stroke. Moreover, the neural basis for and extent to which these cognitive impairments influence functional outcome remains largely unexplored and require additional investigation.